Age estimation in foreign-accented speech by non-native speakers of english - Jiao D; Watson V; Wong SG-J; Gnevsheva K; Nixon JS (Elsevier B.V., 2018)
Listeners are able to very approximately estimate speakers’ ages, with a mean estimation error of around ten years. Interestingly, accuracy varies considerably, depending on a number of social aspects of both speaker and listener, including age, gender and native language or language variety. The present study considers the effects of four factors on age perception. It investigates whether there is a main effect of speakers’ native language (Arabic, Korean and Mandarin) even when speaking a second language, English. It also investigates a particular speaker-listener relationship, namely the degree of linguistic familiarity. Linguistic familiarity was expected to be greater between Mandarin and Korean than between Mandarin or Korean and Arabic. In addition, it considers the effect of the acoustic cues of mean fundamental frequency (F0) and speech rate on age estimates. Fifteen Arabic-accented, fifteen Korean-accented and twenty Mandarin-accented English speakers participated as listeners. They heard audio stimuli produced by forty-eight speakers, equally distributed between native Arabic, Korean and Mandarin speakers, reading a short passage in English. Listeners were instructed to estimate speakers’ ages in years. Listeners’ age estimates and reaction times were recorded. Results indicate a significant main effect of speaker native language on perceived age such that Mandarin speakers were estimated to be younger than Arabic speakers. There was also a significant effect of linguistic familiarity on age estimation accuracy. Age estimates were more accurate with greater linguistic familiarity, i.e., native Korean and Mandarin listeners estimated ages of speakers of their own native languages more accurately than native Arabic speakers’ ages and vice versa. In terms of acoustic cues, mean F0 and speech rate were significant predictors of age estimation. These effects suggest that in perception, age may be marked not only by biological changes that occur over the lifetime, but also by language-specific socio-cultural features.
Keywords: Age estimation; Foreign-accented speech; Non-native listeners; Linguistic familiarity; Acoustic cues of age